1997
DOI: 10.1073/pnas.94.9.4406
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of cardiac α-actin-deficient mice by enteric smooth muscle γ-actin

Abstract: The muscle actins in higher vertebrates display highly conserved amino acid sequences, yet they show distinct expression patterns. Thus, cardiac ␣-actin, skeletal ␣-actin, vascular smooth muscle ␣-actin, and enteric smooth muscle ␥-actin comprise the major actins in their respective tissues. To assess the functional and developmental significance of cardiac ␣-actin, the murine (129͞SvJ) cardiac ␣-actin gene was disrupted by homologous recombination. The majority (Ϸ56%) of the mice lacking cardiac ␣-actin do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
166
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(178 citation statements)
references
References 42 publications
9
166
0
Order By: Relevance
“…This gene encodes cardiac a-actin, and the Actc1 knockout mouse showed a similar phenotype to that of the Itpa À/À mouse. 31 As the Actc1 gene is located near the Itpa gene on mouse chromosome 2, we determined whether Itpa gene disruption affected Actc1 gene expression. Semiquantitative RT-PCR analysis showed that the amount of Actc1 mRNA was not affected by Itpa gene disruption in the heart (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…This gene encodes cardiac a-actin, and the Actc1 knockout mouse showed a similar phenotype to that of the Itpa À/À mouse. 31 As the Actc1 gene is located near the Itpa gene on mouse chromosome 2, we determined whether Itpa gene disruption affected Actc1 gene expression. Semiquantitative RT-PCR analysis showed that the amount of Actc1 mRNA was not affected by Itpa gene disruption in the heart (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Mouse knockouts of cell migration components or other proteins with direct effects on cell migration Protein Function Type Phenotype Reference α skeletal muscle actin Actin Cytoskeleton Total Postnatal death at P1-9, marked loss of body weight; upregulation of other actin isoforms (Crawford et al, 2002) α smooth muscle actin Actin Cytoskeleton Total Viable; impaired vascular contractility and blood pressure homeostasis; upregulation of other actin isoforms (Schildmeyer et al, 2000) α cardiac actin Actin Cytoskeleton Total Perinathal lethality; cardiac hypertrophy and heart muscle abnormalities; upregulation of other actin isoforms (Kumar et al, 1997) β non-muscle actin Actin Cytoskeleton Total Death after E9.5 (Shawlot et al, 1998) γ non-muscle actin Actin Cytoskeleton Skeletal muscle-specific Muscle weakness, necrosis and degeneration (Sonnemann et al, 2006) Tropomyosin Actin Cytoskeleton Total Death before morula stage (Hook et al, 2004) Mena Actin Cytoskeleton Total Viable, with misrouted axons and defects in the nervous system (Lanier et al, 1999) Mena, VASP, Evl triple null Actin Cytoskeleton Total Defects in brain development, neuritogenesis, and neural tube closure Filamin-B Actin Cytoskeleton Total Skeletal malformations and impaired microvascular development (Zhou et al, 2007) Gelsolin (or ADF) Actin Cytoskeleton Total Defects in fibroblast and platelet motility and lamellar responses (Witke et al, 1995) Nonmuscle myosin II-B Actin Cytoskeleton Total Embryonic and perinatal lethality with severe heart defects (Tullio et al, 1997) Myosin heavy chain II-A Actin Cytoskeleton Total Failure in embryonic patterning, embryonic lethality by E7.5 (Conti et al, 2004) Cardiac alpha myosin, heavy chain Actin Cytoskeleton Total Embryonic lethality between E11 and 12 with gross heart defects (Jones, 1996) (Imamoto and Soriano, 1993;Nada et al, 1993) Ephrin B1 Transmembrane signaling Total Neural crest cell misguidance (cranial and cardiac, but not trunk) (Davy et al, 2004) Angiomotin Transmembrane signaling Total Death between E11-E11.5, severe vascular insufficiency in intersomitic regions, dilated vessels in the brain (Aase et al, 2007) Birth Defects Res C Embryo Today. Author manuscript; available in PMC 2009 June 1.…”
mentioning
confidence: 99%
“…aSMA and aCAA are found in primary tumors, whereas aSKA is expressed in the more differentiated state of the rhabdomyosarcomas, consistent with the developmental steps of skeletal muscle differentiation Clement et al, 2003;Moll et al, 2006]. The majority of aCAA KO mice do not survive until birth, and those that survive, die within 2 weeks after birth [Kumar et al, 1997]. Apart from occasional delay, the development of the embryonic aCAA deficient hearts is normal up to E14.0 [Abdelwahid et al, 2004].…”
Section: Mutations In Aska Cause Various Congenital Myopathiesmentioning
confidence: 75%
“…But the total actin content in the heart is still reduced by about 50%. Increase of the total actin content to normal levels was achieved by ectopic expression of gSMA under the control of the cardiac a-myosin heavy chain promoter in these aCAA deficient mice [Kumar et al, 1997]. These transgenic mice can reach adulthood, but their hearts are hypodynamic, enlarged and hypertrophied [Kumar et al, 1997].…”
Section: Mutations In Aska Cause Various Congenital Myopathiesmentioning
confidence: 99%
See 1 more Smart Citation